Potential application of traditional Chinese medicine in cerebral ischemia-Focusing on ferroptosis - Fengyan Zhao; Fengyan Zhao; Fengyan Zhao; Caiwang Peng; Caiwang Peng; Caiwang Peng; Yang Sun; Yang Sun; Yang Sun; Hengli Li; Hengli Li; Hengli Li; et al. (Frontiers Media S.A., 2022)
Traditional Chinese medicine (TCM) has attracted a great deal of attention in the treatment of cerebral ischemia is credited with the remarkable neuroprotective effects. However, the imperfect functional mechanism of TCM is a major obstacle to their application. Many studies have been conducted to illustrate the pathophysiology of post-ischemic cerebral ischemia by elucidating the neuronal cell death pathway. Meanwhile, a new type of cell death, ferroptosis, is gradually being recognized in various diseases and is becoming a new pathway of therapeutic intervention strategy to solve many health problems. Especially since ferroptosis has been found to be closely involved into the pathogenesis of cerebral ischemia, it has been considered as a key target in the treatment of cerebral ischemia. Therefore, this paper reviews the latest research findings about the treatment of cerebral ischemia with TCM focused on ferroptosis as a target. Also, in order to explores the possibility of a new approach to treat cerebral ischemia with TCM, we discusses the correlation between ferroptosis and other cell death pathways such as apoptosis and autophagy, which would provide references for the following researches.